PENINGKATAN KETERAMPILAN DAN PRODUKTIVITAS CABAI KELOMPOK PETANI BERBASIS PENERAPAN AGROVOLTAIC: IMPLEMENTASI MITIGASI PERUBAHAN IKLIM - Syahrullah Syahrullah; Tenri Sau (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
Climate change not, eliminate coal and oil-fueled vehicles will be substituted for electric vehicles. In the future, it is predicted that there will be more government policies to create innovations related to climate change mitigation and adaptation. Therefore, innovations and environmentally friendly technology breakthroughs are needed in every industrial and MSME management activity, one of which is the production and management of rice plants. This service activity aims to substitute the use of chemical fertilizers for the use of environmentally friendly fertilizers through activities to increase farmer group skills and productivity of rice plants based on Agrovoltaic innovation and technology. The implementation method begins with observation activities, program planning, implementation of training/assistance activities for making Agrovoltaic and then ends with monitoring and evaluation activities. The result of this program is the application of environmentally friendly innovation, namely Agrovoltaic technology in Mentoring activities to participants of the Pada Idi farmer group members so that they are able to improve the skills of farmer groups (100%) in utilizing agricultural waste into fertilizer that is very useful, cheap and environmentally friendly so that it has an impact on increasing land productivity and the balance of environmental ecosystems around rice fields. The range for the increase in rice production is 15% from the previous production data